Restorative Justice In Application For Crime Investigation Abuse In Polsek Middle Semarang - M.Gargarin Friyandi; Aryani Witasari (Jurnal Daulat Hukum, 2019)
The issues that will be reviewed by the authors in this paper are: 1) How can the application of Restorative Justice in the criminal investigation police persecution in the Middle Semarang?; 2) What are the obstacles in the implementation of Restorative Justice in the criminal investigation police persecution in the Middle Semarang; 3) What is the solution to implement Restorative Justice in the criminal investigation police persecution in the Middle Semarang? The method research approach used socio-juridical. Specification of the research is descriptive.The the type of data used is primary data, secondary data consisting of secondary legal materials and tertiary legal materials.Based on the results of the study concluded that the application of Restorative Justice in the investigation of criminal mistreatment in police Middle semarang has been able to implement, but still refer to the existing rules that reduce the evidence to the non-fulfillment of the evidence in accordance with Article 184 Criminal Procedure Code so that the case can be implemented degrees termination of an investigation or SP3 , Obstacles in the implementation of Restorative Justice in the criminal investigation police persecution in the Middle Semarang is the existence of internal factors and external factors that should be corrected so that Restorative Justice can be implemented without violating the rules. The barriers related solutions need to do is provide legal counseling, seminars, maximize the role of lower-level government officials related legal awareness in the community and maximize Bhabinkamtibmas role as the executive officer as well as representing the presence of the state in society.Keywords: Restorative justice; Investigation; Crime of Persecution.